Predictive Value of Ki-67 Index in Evaluating Sporadic Vestibular Schwannoma Recurrence: Systematic Review and Meta-analysis - Vakharia, Kunal; Hasegawa, Hirotaka; Graffeo, Christopher; Noureldine, Mohammad H. A.; Cohen-Cohen, Salomon; Perry, Avital; Carlson, Matthew L.; Driscoll, Colin L. W.; Peris-Celda, Maria; Van Gompel, Jamie J.; Link, Michael J. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Introduction Ki-67 is often used as a proliferation index to evaluate how aggressive a tumor is and its likelihood of recurrence. Vestibular schwannomas (VS) are a unique benign pathology that lends itself well to evaluation with Ki-67 as a potential marker for disease recurrence or progression following surgical resection.Methods All English language studies of VSs and Ki-67 indices were screened. Studies were considered eligible for inclusion if they reported series of VSs undergoing primary resection without prior irradiation, with outcomes including both recurrence/progression and Ki-67 for individual patients. For published studies reporting pooled Ki-67 index data without detailed by-patient values, we contacted the authors to request data sharing for the current meta-analysis. Studies reporting a relationship between Ki-67 index and clinical outcomes in VS for which detailed patients' outcomes or Ki-67 indices could not be obtained were incorporated into the descriptive analysis, but excluded from the formal (i.e., quantitative) meta-analysis.Results A systematic review identified 104 candidate citations of which 12 met inclusion criteria. Six of these studies had accessible patient-specific data. Individual patient data were collected from these studies for calculation of discrete study effect sizes, pooling via random-effects modeling with restricted maximum likelihood, and meta-analysis. The standardized mean difference in Ki-67 indices between those with and without recurrence was calculated as 0.79% (95% confidence interval [CI]: 0.28–1.30; p = 0.0026).Conclusion Ki-67 index may be higher in VSs that demonstrate recurrence/progression following surgical resection. This may represent a promising means of evaluating tumor recurrence and potential need for early adjuvant therapy for VSs.
Keywords: histopathology; vestibular schwannoma; acoustic neuroma; recurrence; progression; Ki-67; index; systematic review; meta-analysis